FAKTOR-FAKTOR DETERMINAN TINGKAT DISABILITAS PADA PASIEN DEWASA DAN LOW BACK PAIN - Linfeng, Gao; Liena, Liena; Wienaldi, Wienaldi (Jurnal Keperawatan dan Kesehatan, 2026)
Background: Low Back Pain (LBP) is one of the musculoskeletal disorders that is a major cause of disability globally. The level of disability due to LBP is influenced by various individual and behavioral factors. Objective: This study aimed to analyze the factors associated with the level of disability in patients with Low Back Pain at the Orthopedic Clinic of Royal Prima Hospital in Medan in 2025. Methods: This study used a quantitative analytical design with a cross-sectional approach. The study sample consisted of 120 respondents selected using purposive sampling. Data were collected through interviews using questionnaires, Body Mass Index (BMI) measurements, and disability level assessments using the Oswestry Disability Index (ODI). Data analysis was performed using bivariate analysis with the Chi-square test and multivariate analysis using binary logistic regression. Results: The results showed that most respondents experienced moderate to severe disability (78.3%). Bivariate analysis showed a significant relationship between age (p=0.018), BMI (p=0.032), duration of sitting per day (p=0.006), and level of physical activity (p=0.004) with the level of disability. Patients aged ≥45 years, with overweight or obese BMI, sitting duration of more than 6 hours per day, and low physical activity tended to experience more severe disability. Meanwhile, gender did not show a significant relationship with disability level (p=0.210). Multivariate analysis results showed that low physical activity was the most dominant factor associated with disability levels (OR=4.58; 95% CI: 1.79–11.69). Conclusion: This study indicates that physical activity plays an important role in determining disability levels in patients with low back pain.